Assessing Repeated Oxalic Acid Vaporization in Honey Bee (Hymenoptera: Apidae) Colonies for Control of the Ectoparasitic Mite Varroa destructor. Issue 1 (7th February 2022) - Berry, Jennifer A; Bartlett, Lewis J; Bruckner, Selina; Baker, Christian; Braman, S Kris; Delaplane, Keith S; Williams, Geoffrey R
Abstract: The American beekeeping industry continually experiences colony mortality with annual losses as high as 43%. A leading cause of this is the exotic, ectoparasitic mite, Varroa destructor Anderson & Trueman (Mesostigmata: Varroidae). Integrated Pest Management (IPM) options are used to keep mite populations from reaching lethal levels, however, due to resistance and/or the lack of suitable treatment options, novel controls for reducing mites are warranted. Oxalic acid for controlling V. destructor has become a popular treatment regimen among commercial and backyard beekeepers. Applying vaporized oxalic acid inside a honey bee hive is a legal application method in the U.S., and results in the death of exposed mites. However, if mites are in the reproductive stage and therefore under the protective wax capping, oxalic acid is ineffective. One popular method of applying oxalic is vaporizing multiple times over several weeks to try and circumvent the problem of mites hiding in brood cells. By comparing against control colonies, we tested oxalic acid vaporization in colonies treated with seven applications separated by 5 d (35 d total). We tested in apiaries in Georgia and Alabama during 2019 and 2020, totaling 99 colonies. We found that adult honey bees Linnaeus (Hymenoptera: Apidae), and developing brood experienced no adverse impacts from the oxalic vaporization regime. However, we did not find evidence that frequent periodic application of oxalic during brood-rearing periods is capable of bringing V. destructor populations below treatment thresholds.